An Integrative Model to Verify the Impact of Strategic Direction and Institutional Entrepreneurial Awareness Role As a Moderating Factor in Promoting Competitive Advantages: A Field Study - Al mawadieh, yousef (Jordan Journal of Business Administration, 2019)
This study aims to develop an integrative model that measures the relationship between the independent variables presented by the strategic directions and their dimensions. This is done through the moderating variable represented by entrepreneurial awareness with its dimensions. The study used the analytical correlative survey approach, as it is the most appropriate method to resolve the study's problem. The study population was made up of all Jordanian companies that received King Abdallah II Award for Excellence, totaling 37 companies. Due to the small size of the study population, a comprehensive survey was conducted for all of the Jordanian companies that received King Abdallah II Award for Excellence. 400 questionnaires were distributed, 324 of which were collected, analyzed and statistically evaluated. The study concluded that there is a statistically significant impact for strategic direction on promoting competitive advantages through entrepreneurial awareness as a modifying factor among the companies that have received King Abdallah II Award for Excellence. This indicates that the Jordanian companies that have received this award are working on enhancing their competitive position through strategic direction and entrepreneurial awareness. The study recommends the adoption of entrepreneurial awareness as a continuous and integrated work methodology to support competitiveness in Jordanian companies.